2020
DOI: 10.7250/bjrbe.2020-15.497
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Modulus of Deformation Determined by Static and Dynamic Plate Load Tests

Abstract: Soil, or soil structure modulus of deformation, is one of the main design parameters for road engineering and traffic infrastructure design of, for example, highways, railways, runways and embankments. It is also the main soil improvement criterion. When creating any road structure with codified design resistance, one employs structural layers of certain thicknesses and modulus of deformation. Both values need to satisfy the minimum values in accordance with codified requirements. This paper analyzes correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The study also suggested Influence of Biaxial Geogrid at the Ballast Interface for Granular Earth Railway Embankment no effect of boundary on the FEM model while calculating the second deformation modulus numerically. Lehmann et al (2020) suggested both plate load and lightweight deflectometer tests were essential at a site and correlations should not be used to convert from the second modulus to dynamic modulus or vice-versa in the absence of tests. There are numerous studies present in the literature that establish the importance of the soil modulus for earth embankments.…”
Section: Introductionmentioning
confidence: 99%
“…The study also suggested Influence of Biaxial Geogrid at the Ballast Interface for Granular Earth Railway Embankment no effect of boundary on the FEM model while calculating the second deformation modulus numerically. Lehmann et al (2020) suggested both plate load and lightweight deflectometer tests were essential at a site and correlations should not be used to convert from the second modulus to dynamic modulus or vice-versa in the absence of tests. There are numerous studies present in the literature that establish the importance of the soil modulus for earth embankments.…”
Section: Introductionmentioning
confidence: 99%